Cross cultural differences in tax compliance behavior at different tax rates: Experimental evidence with samples from Argentina and Spain - Tanos Robein, Lucas (2020)
The aim of this study was to analyze the role of different socioeconomic backgrounds in tax compliance behavior at different tax rates. Additionally, we examine the effect of the source of income (whether if it is earned or endowed) on tax behavior. In the first study, students from Argentina and Spain performed an anagram task to earn profits and then they declared their earnings at different tax rates. In the second study, students from Argentina were endowed with an income at the beginning of the experiment and then they declared their earnings at different tax rates. Significant cross-cultural differences were observed at high tax rates. Also, when income was earned, participants declared significant more than when de income was endowed. The results show the importance to consider sociocultural aspects when making public policy and the role of income source in tax behavior.